Ecospiritual Traits in the Animation Movies Brother Bear and Pocahontas - Vijayan, Karthika P.; Pai , Geetha R. (International Journal of Psychosocial Rehabilitation, 2020)
Today there is a rise in the atrocities perpetrated against nature. With the progress in science and technology, the standard of living has improved, but at the same time the relation that man has with nature is deteriorating. In the earlier times, man used to resort to nature for each and every one of his needs, but now he is plundering her for his benefits. It is in such a scenario that theories like ecocriticism, deep ecology, etc. have developed. Ecospirituality is an offshoot of the ecocriticism theory. Ecospirituality tries to establish a spiritual bond between the man and the nature. This paper is an attempt at the analysis of two animation movies, Brother Bear and Pocahontas produced by Walt Disney with the afore-mentioned theory. Both these movies beautifully capture the divine link that man and nature share. Both the movies are set in the United States of America, and make use of several Native American myths. It can be seen that both the nature and the spirituality are an integral part of the Native American culture. With the help of these movies, it can be said that the link between the nature and the man is everlasting, and that it is the need of the hour to remind man to protect and respect Mother Earth and her creations.